Buy-in : saving your good idea from getting shot down - Kotter, John P., 1947-; Whitehead, Lorne A. (Boston, Mass. : Harvard Business Review Press, 2010)
Explains how to effectively present and carry through one's business idea, focusing on the key areas of contention that opponents will offer and detailing how to combat each of them.
The Centerville story. The death of a good plan -- Saving the day in Centerville, part one -- Saving the day in Centerville, part two -- Saving the day in Centerville, part three -- The method. Four ways to kill a good idea -- A counterintuitive strategy for saving your good idea -- Twenty-four attacks and twenty-four responses -- A quick reference guide for saving good ideas.
Description based on print version record.
Keywords: Sales promotion; Creative ability in business; Public relations; Creative ability in business; Public relations; Sales promotion; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; elektronické knihy; electronic books